On Travails and Triumphs: A Mixed-Method Exploration of Public Speaking Experiences Among Senior High School Students in Hagonoy - Marfil, Conelyn; Rulona, Maritess (Journal of Interdisciplinary Perspectives, 2025)
Impromptu speaking is a vital skill that enhances students’ ability to communicate effectively in various academic and real-world contexts. This study examined the difficulties and coping mechanisms of Grade 11 Technical Vocational Livelihood (TVL) track students at Hagonoy National High School in impromptu speaking. Using a mixed-method approach, surveys were conducted with 236 students, and eight were interviewed for deeper insights. The study assessed six key linguistic factors: organization of ideas, coherence and cohesion, verb usage, confidence and delivery, time management, and proper punctuation and intonation. Results indicated that students faced moderate challenges across all areas, particularly in structuring ideas, using correct grammar, and maintaining fluency under pressure. Key struggles included difficulty in organizing thoughts, reliance on simple vocabulary, and hesitations in speech. Additionally, fear of judgment and anxiety contributed to their speaking difficulties. To cope, students practiced independently, simplified their speech, and focused on key points. Some sought peer support or used relaxation techniques to manage speaking anxiety. Emerging themes highlighted students' adaptability, self-reliance, and determination in overcoming challenges related to impromptu speaking. Beyond immediate speaking improvements, impromptu speaking fosters readiness for future academic and professional settings by enhancing confidence, emotional control, and listening skills. Findings underscored the need for targeted interventions, such as structured speaking activities, tailored instructional strategies, and supportive learning environments. Addressing these gaps will significantly enhance students’ communication skills, leading to improved academic performance and better career preparedness. This study provides valuable insights into enhancing impromptu speaking support within educational settings, highlighting the importance of structured guidance in helping students develop their speaking skills effectively.